Simultaneous optical and electrochemical label-free biosensing with ITO-coated lossy-mode resonance sensor - Śmietana, Mateusz; Koba, Marcin; Sezemsky, Petr; Szot-Karpińska, Katarzyna; Burnat, Dariusz; Stranak, Vitezslav; Niedziółka-Jönsson, Joanna; Bogdanowicz, Robert (Biosensors & bioelectronics, 2020)
In this work we discuss a new label-free biosensing device based on indium tin oxide (ITO) overlaid section of a multimode optical fiber fused silica core. The sensor has been used to optical measurements also simultaneously interrogated electrochemically (EC). Due to optimized thickness and optical properties of ITO film, a lossy-mode resonance (LMR) could be observed in the optical domain, where electrical properties of the film allowed for application of the sensor as a working electrode in an EC setup. It has been confirmed that the LMR response depends on optical properties of the external medium, as well as potential applied to the electrode during cyclic voltammetry. After the ITO surface functionalization with amine groups and covalently attached biotin, the device has been applied for label-free biosensing of avidin in both the domains simultaneously. On the example of biotin-avidin detection system it was demonstrated that when avidin concentration increases a decrease in current and increase in LMR wavelength shift were recorded in EC and optical domain, respectively. Both optical and EC responses follow the protein interaction process, and thus can be used as cross-verification of the readouts. Moreover, an extended information has been achieved comparing to solely EC interrogation, i.e., the grafting process of biotin and avidin was directly monitored optically displaying individual steps of an incubation procedure.
Keywords: Electrochemical Techniques; optika a fotonika; avidin; Optics and Photonics; Tin Compounds; Biotin; Biosensing Techniques; sloučeniny cínu; biotin; Label-free biosensing; Electrodes; Indium tin oxide (ITO); Electrochemistry; Avidin; elektrochemické techniky; biosenzitivní techniky; Multi-domain sensing; Thin film; elektrody; Lossy-mode resonance; Optical fiber sensor